2002
DOI: 10.1111/j.1651-2227.2002.tb02851.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐classical 21‐hydroxylase deficiency in children: association of adrenocorticotropic hormone‐stimulated 17‐hydroxyprogesterone with the risk of compound heterozygosity with severe mutations

Abstract: Aim: To investigate the association between levels of 17‐hydroxyprogesterone (17‐OHP) and the risk of being compound heterozygous for severe mutations in children with non‐classical 21‐hydroxylase deficiency (NC21OHD). Methods: In 86 Spanish NC21OHD children (75 families) an analysis of the 21‐hydroxylase (21‐OH) gene was performed by CYP21B‐specific polymerase chain reaction amplification, allele‐specific oligonucleotide hybridization and Southern blotting. Familial analysis established how the alleles segreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 23 publications
1
7
2
Order By: Relevance
“…Moreover, as previously reported, NC 21OHD patients that are compound heterozygotes for a severe pathogenic variant present higher levels of ACTH-stimulated 17OHP than homozygotes/compound heterozygotes for milder alleles [34]. …”
Section: Discussionsupporting
confidence: 51%
“…Moreover, as previously reported, NC 21OHD patients that are compound heterozygotes for a severe pathogenic variant present higher levels of ACTH-stimulated 17OHP than homozygotes/compound heterozygotes for milder alleles [34]. …”
Section: Discussionsupporting
confidence: 51%
“…Homozygosity for mild mutations was found in 52.7% of our patients, a percentage strikingly higher than that recently reported in a large series of French adult patients (26) and in previous studies in adult Brazilian patients (23), but similar to the one detected in pediatric Spanish (29) and Jewish patients (30), mostly comprised of children with PP. These different figures cannot be related to the different ethnicity of the populations studied, as the majority of the patients are of Caucasian origin.…”
Section: Discussioncontrasting
confidence: 42%
“…The CYP21A2 genotyping of the 55 children affected by NCCAH showed that, as in other series, the most frequently observed mutation is V281L (23,29,30). Homozygosity for mild mutations was found in 52.7% of our patients, a percentage strikingly higher than that recently reported in a large series of French adult patients (26) and in previous studies in adult Brazilian patients (23), but similar to the one detected in pediatric Spanish (29) and Jewish patients (30), mostly comprised of children with PP.…”
Section: Discussionmentioning
confidence: 99%
“…Native acrylamide/bisacrylamide minigels were used to detect the 8-bp deletion. Complementary confirmatory sequencing of coding regions and intron-exon boundaries was also performed as previously described (8,17). Parental DNAs were also studied to determine allele segregation; this was further examined by complementary microsatellite typing (18,19) involving the highly informative D6S273 and D6S439 markers plus two intragenic intronic polymorphisms at tumor necrosis factor alpha and TAP1 (genes in the HLA region).…”
Section: Molecular Studiesmentioning
confidence: 99%
“…Some countries include this disorder in neonatal screening programs. The NC forms, which are associated with signs of hyperandrogenism, were initially described in adult women and only more recently in pediatric patients (4)(5)(6)(7)(8). Precocious pubarche and bone age advancement are typical in children; women may suffer hirsutism, acne, irregular menses, polycystic ovaries, and infertility.…”
mentioning
confidence: 96%